Effect of Occupational Health and Safety Management and Employee Turnover Intention: A Comparative Study in Pakistan’s Mining Industry - Mohsin Ali Shaikh; Song Weiguo; Usman Shahid; Rehmat Karim (SAGE Open, 2025)
The mining industry is one of the most dangerous industries and requires comprehensive occupational health and safety management to protect the mining industry employees. However, occupational accidents greatly influence employee turnover in the mining industry. Following the predictive study approach, a cross-sectional survey was designed to collect quantitative data from 275 workers in the mining industry. The data were analysed using standardized questionnaires, multiple regression, multi-collinearity tests, means, and standard deviation methods. The results show that the correlation coefficient revealed a negative association between occupational health and safety elements such as safety training ( r  = −.31, p  < .01), safety leadership ( r  = −.28, p  < .01), fire safety ( r  = −.33, p  < .01), safety measure ( r  = −.25, p  < .01), and the likelihood of turnover. Safety training (β = −.32, p  < .01) and fire safety (β = −.231, p  < .01) were shown to be critical indicators of employee turnover. Our findings suggest that safety training and fire safety play a pivotal role in occupational health and safety to minimize employee turnover in the mining industry of Pakistan. It was concluded that this study provides a better understanding to improve mining sectors and help to reduce the high employee turnover intention in the mining industry. The study also suggests that improving safety training and fire safety could reduce employee turnover and enhance workers’ well-being in the mining industry.